Organ donation: reducing the risk of health care‐associated infection. Issue 3 (26th September 2018) - Bleakley, Greg; Cole, Mark
ABSTRACT: Health care‐associated infection is a real and relative risk within the realm of organ donation. Despite detailed guidance from the Advisory Committee on the Safety of Blood, Tissues and Organs on the microbiological safety of human organs, tissues and cells used in transplantation, the topic has received limited exposure in the literature. This paper will give a context to the Safety of Blood, Tissues and Organs guidance, outline the key recommendations for mandatory/recommended screening and provide a summary of infections that may be present at the time of donation that require careful risk assessment. This does not detract from national guidelines and cannot replace expert advice but will raise awareness and complement safe and effective care delivery.